2007
DOI: 10.1128/aac.00905-07
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Resistance Study of Rupintrivir, a Novel Inhibitor of Human Rhinovirus 3C Protease

Abstract: Rupintrivir (formerly AG7088) is an irreversible inhibitor of the human rhinovirus (HRV) 3C protease that has been demonstrated to have in vitro activity against all HRVs tested, consistent with its interaction with a strictly conserved subset of amino acids in the 3C protease. The potential for resistance was studied following in vitro serial passage of HRV serotypes 14, 2, 39, and Hanks in the presence of increasing rupintrivir concentrations. HRV variants with reduced susceptibilities to rupintrivir (sevenf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
37
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 32 publications
5
37
0
1
Order By: Relevance
“…The reverseengineered double mutant had a level of resistance (3-fold) comparable to that of the phenotypically selected variant. It has been reported that in vitro-selected rupintrivir-resistant RV14 (7-to 16-fold resistant) carries four substitutions (i.e., T129A, T131A, Y139H, T143P) in 3C (21). Even though the quadruple mutant also carries a substitution at position 143 (21), we did not observe cross-resistance between SG85 (which selects for the substitutions S127G and T143A) and rupintrivir ( Table 2).…”
mentioning
confidence: 50%
“…The reverseengineered double mutant had a level of resistance (3-fold) comparable to that of the phenotypically selected variant. It has been reported that in vitro-selected rupintrivir-resistant RV14 (7-to 16-fold resistant) carries four substitutions (i.e., T129A, T131A, Y139H, T143P) in 3C (21). Even though the quadruple mutant also carries a substitution at position 143 (21), we did not observe cross-resistance between SG85 (which selects for the substitutions S127G and T143A) and rupintrivir ( Table 2).…”
mentioning
confidence: 50%
“…A previous study identified several mutations in human rhinoviruses (HRVs) that confer resistance to treatment with rupintrivir, including the T129/130, T131, T143, N165, N130, and L136 mutations (39). By checking the crystal structure of EV71 3C pro (40), the N69S substitution unexpectedly appears to be close to but outside the active site of EV71 3C pro (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As rupintrivir was developed as an inhibitor of the 3C protease of human rhinoviruses (7,8), we assessed its potential of inhibiting the 3C-like protease of Norwalk virus by molecular modeling, based on the crystal structure of the free enzyme (11). The active site of the Norwalk virus protease bears similarities to that of the enterovirus 3C proteases (30,31); the catalytic triad is formed by residues Cys139, His30, and Glu54 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Rupintrivir was initially developed as an intranasal product to treat rhinovirus infections (7,8). Given its poor oral bioavailability, the molecule does not have the ideal pharmacokinetics profile for a prophylactic approach to prevent norovirus infections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation